Synthesis and antiproliferative activity in vitro of amidino substituted 2-phenylbenzazoles - Racané, Livio (Array, 2019)
Within this work we describe the synthesis of versatile substituted 2-phenyl benzothiazole 3–10 and 2-phenylbenzimidazole 12–19 derivatives bearing amidino groups. Furthermore, the synthesized compounds were explored for their antiproliferative activity in vitro on three cancer cell lines. Tested compounds showed moderate to strong antiproliferative activity. Furthermore, the type of the attached amidino group on benzazole nuclei has the significant impact on the antiproliferative activity only within benzimidazole derivatives with 2-imidazolinyl substituted derivatives being more active in comparison to amidino substituted analogues. All obtained results revealed that this type of benzothiazole derivatives have a great potential for further optimization and development of more efficient potential antiproliferative agents.